2020
DOI: 10.3389/fninf.2020.610967
|View full text |Cite
|
Sign up to set email alerts
|

Review of Deep Learning Approaches for the Segmentation of Multiple Sclerosis Lesions on Brain MRI

Abstract: In recent years, there have been multiple works of literature reviewing methods for automatically segmenting multiple sclerosis (MS) lesions. However, there is no literature systematically and individually review deep learning-based MS lesion segmentation methods. Although the previous review also included methods based on deep learning, there are some methods based on deep learning that they did not review. In addition, their review of deep learning methods did not go deep into the specific categories of Conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 58 publications
0
48
0
7
Order By: Relevance
“…After binarizing the probability maps, the dice coefficient was for the test data, which is comparable to the intra-observer variability of the manual drawer ( ) and is comparable to literature (0.47–0.95). [ 33 , 36 ] The CNN might be more robust compared with manual annotations because the network has no variations for multiple annotations. We have shown that the network only predicts lesion probability maps for the loss functions MAE and MSE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After binarizing the probability maps, the dice coefficient was for the test data, which is comparable to the intra-observer variability of the manual drawer ( ) and is comparable to literature (0.47–0.95). [ 33 , 36 ] The CNN might be more robust compared with manual annotations because the network has no variations for multiple annotations. We have shown that the network only predicts lesion probability maps for the loss functions MAE and MSE.…”
Section: Discussionmentioning
confidence: 99%
“…[ 33 ] To overcome these limitations of manual segmentation, different DL architectures and networks have been used, yielding dice coefficients ranging from 0.48 to 0.95 for WM lesion segmentation. [ 33 36 ] Therefore, in a recent publication, it was shown that the use of regression networks for generating distance maps of the lesions might improve the WM lesion segmentation process [ 37 ]. This could provide more information about lesion geometry, structure, and changes similar to lesion probability mapping.…”
Section: Introductionmentioning
confidence: 99%
“…After binarizing the probability maps, the dice coefficient was 0.61 ± 0.09 for the test data, which is comparable to the intra-observer variability of the manual drawer (0.68 ± 0.23) and is comparable to literature (0.47-0.95). [33,36] The CNN might be more robust compared with manual annotations because the network has no variations for multiple annotations. We have shown that the network only predicts lesion probability maps for the loss functions MAE and MSE.…”
Section: Discussionmentioning
confidence: 99%
“…This is an information gain compared to manual annotators and compared to lesion segmentation methods based solely on the quantitative parametric maps. [36,37] In further work, this has to be compared with conventional methods for assessing these components such as the myelin or extracellular water. [43,45,46] This study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation